I need help with proving the partial sum formula for the following series with induction: $$ \sum^\infty_{n=1}\frac{n}{(n+1)!}$$ I found a partial sum formula for the series: $$S_n=1-\dfrac{1}{(n+1)!}$$ I am stuck on proving the partial sums with induction.

My attempt is:

For the base case:

$S_1=\dfrac{1}{2}$ Next assume true for k: $$S_k=\dfrac{k}{(k+1)!}$$ However, at this point I am not sure how to proceed with proving $k+1$, if someone could give me some pointers that would be awesome.


Let $a_k = \frac{k}{(k+1)!}$ be the $k^{\mathrm{th}}$ term. Your hypothesis is that $S_n = 1-\frac{1}{(n+1)!}$ for all $n$. Given your inductive hypothesis, it is enough to show that $$ S_{k+1} = S_k + a_{k+1} = 1-\frac{1}{(k+1)!} + \frac{k+1}{(k+2)!} = 1-\frac{1}{(k+2)!}.$$ This is a calculation that I suspect you can perform.

  • $\begingroup$ Makes sense, thanks for the fast reply! $\endgroup$ – modimagni Apr 15 '14 at 0:43
  • 1
    $\begingroup$ The hypothesis is that $$S_n = 1 - \frac{1}{(n+1)!}$$ for all $n \leq k$. If the OP had it for all $n$, they'd be done (i.e., that would mean the induction argument was already finished). $\endgroup$ – Nicholas Stull Apr 15 '14 at 0:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.